PRODUCTION OF PHREATIC EXPLOSIONS IN THE INTERACTION OF LAVA AND ICE - Vinogradov V.N.; Muravyev Y.D.; Nikitina I.M.; Salamatin A.N. (My University, 1990)
A matematical model is given of the formation of phreatic explosions in lava flows coming into contact with ice formations. Quantitative characteristics are derived for the various stages in the development of the explosion; by means of wich its strength and other parameters may be evaluated. The theoretical calculation results are in agreement with empirical data.
Keywords: 28.17.23 Моделирование физических процессов; 37.01.77 Методы исследования и моделирования. Математические и кибернетические методы; 37.29.35 Современное оледенение; Ключевской